The Institutional and External Factors Behind the Switch of a Country’s Economic Growth Strategy. The Case of the Brazilian Economic Policy - Czarnecka-Gallas Marta (International Journal of Management and Economics, 2015)
One of the most important tasks for Brazil after the Second World War was to change the structure of its economy. Due to a relatively low level of domestic industry, consecutive governments found industrialization the main priority and focused on industrial policy to foster that process. One can argue that industrial policy was the core element of Brazilian economic policy throughout the post-war period, until the liberalization reforms of the 1980 s. Political and economic traditions, together with rapid changes in global economy over the last decades, have had a huge impact on more recent Brazilian economic policy. On one hand, the country has kept looking back to the protectionist practices that have shaped its economy since the emergence of the modern Brazilian state, on the other, Brazil’s ambition is to become a leading emerging economy and serious partner in the developed world. A dual development track, and continuous inner-conflict between protectionism and liberalism, is clearly visible in Brazilian economic policy and often leads to contradictory measures being taken by successive governments. The objectives of the article is to provide a contextualized analysis of the evolution of Brazil’s economic growth strategy, with a particular focus on the role of economic and political traditions, and institutions.